2022
DOI: 10.3389/fmars.2022.895995
|View full text |Cite
|
Sign up to set email alerts
|

Siliceous Rhizaria abundances and diversity in the Mediterranean Sea assessed by combined imaging and metabarcoding approaches

Abstract: Siliceous Rhizaria (polycystine radiolarians and phaeodarians) are significant contributors to carbon and silicon biogeochemical cycles. Considering their broad taxonomic diversity and their wide size range (from a few micrometres up to several millimetres), a comprehensive evaluation of the entire community to carbon and silicon cycles is challenging. Here, we assess the diversity and contribution of silicified Rhizaria to the global biogenic silica stocks in the upper 500 m of the oligotrophic North-Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This computation was chosen to prevent overestimation of the individual's biovolume, due to unfolded copepods' antennae for example (as done in Monferrer et al., 2022). Then, each individual biovolume was multiplied by its density factor d to account for the water volume sampled, and a taxonomic‐specific factor t to get the individual dry weight from individual biovolume value.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This computation was chosen to prevent overestimation of the individual's biovolume, due to unfolded copepods' antennae for example (as done in Monferrer et al., 2022). Then, each individual biovolume was multiplied by its density factor d to account for the water volume sampled, and a taxonomic‐specific factor t to get the individual dry weight from individual biovolume value.…”
Section: Methodsmentioning
confidence: 99%
“…While both metabarcoding and imaging techniques can provide information on the temporal and spatial distribution of zooplankton communities and their environmental dynamics (Vilgrain et al., 2021), imaging data is also able to quantify taxa's abundance and biomass (e.g., Monferrer et al., 2022). Hence, it would be ideal to combine high throughput image acquisition methods with metabarcoding to improve zooplanktonic community studies (Bucklin et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The access to this environment allowed them to become important contributors to the planktonic food web of an ecosystem with potentially low predators. However, caution is required when interpreting metabarcoding data [59, 60]. Life cycle of Radiolaria remains poorly understood, with the belief that the release of small bi-flagellated cells (referred to as swarmers) by mature cells plays a role in their reproductive cycle [61, 62].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, taxonomists have been able to greatly refine the understanding of evolutionary relationships amongst these diverse protists (Aurahs et al, 2009; Biard et al, 2015; Cavalier-Smith et al, 2018; Decelle et al, 2013, 2012; rev by Biard, 2022a). DNA metabarcoding studies have revealed insights into the distributional patterns (Biard et al, 2017; Blanco-Bercial et al, 2022; Decelle et al, 2013; Llopis Monferrer et al, 2022; Mars Brisbin et al, 2020; Sogawa et al, 2022), ecological relationships (Decelle et al, 2012; Nakamura et al, 2023), and contribution to biogeochemical fluxes (Guidi et al, 2016; Gutierrez-Rodriguez et al, 2019). Transcriptomic and proteomic approaches also have been used to quantify Rhizaria contribution to community metabolism (Cohen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%